2023
DOI: 10.1037/ppm0000429
|View full text |Cite
|
Sign up to set email alerts
|

The prosocial and cathartic potential of immersive media on eudaimonic entertainment experiences.

Abstract: Recent scholarship in media entertainment supports the potential of meaningful and thought-provoking or eudaimonic narratives to facilitate a host of positive outcomes including elevation, catharsis, and altruism. Although the prosocial impact of such content has been examined in a variety of contexts including TV, films, video games, and social networking sites, researchers have yet to fully understand the influence of immersive storytelling on users' eudaimonic entertainment experiences. Using a 2 (Immersion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Finally, in one of the latest studies using 360-degree video that also compares the impact of traditional and immersive media, Chen et al (2022) focus on the capabilities of eudaimonic storytelling to elicit elevation and catharsis as mediators of positive behavioral outcomes such as altruism. Their findings identify elevation as a mediator between thought-provoking content and altruistic motivation.…”
Section: Standardizing the Experimental Methods And Decision-making S...mentioning
confidence: 99%
“…Finally, in one of the latest studies using 360-degree video that also compares the impact of traditional and immersive media, Chen et al (2022) focus on the capabilities of eudaimonic storytelling to elicit elevation and catharsis as mediators of positive behavioral outcomes such as altruism. Their findings identify elevation as a mediator between thought-provoking content and altruistic motivation.…”
Section: Standardizing the Experimental Methods And Decision-making S...mentioning
confidence: 99%
“…The impact of joy on immersion and willingness to pay in virtual reality (VR) environments has been an intriguing topic of recent research. Studies have found that joy, as an emotional state, can significantly influence individuals' immersion in VR experiences [202][203][204]. This suggests that joy not only contributes to immersion but also intertwines with the rich emotional experience of VR.…”
Section: The Influence Of Joy On Immersion and Intention To Paymentioning
confidence: 99%